UiTM student’s timetable manager for android (UTiMa) - Abd. Nasir, Syamsul Aiman
Throughout the development, there are times when idea suddenly pops up, and suggestions keep on coming. Some of the ideas and suggestions are admittedly brilliant as well as useful, due to expertise limitations and time constraint, these add – on second tier features is being dropped from the final product of the project. However, should anybody is interested in continuing the project, in order to improve or revamp the application; these are some recommendations to improve the overall usability of the application. The first suggestion is to introduce ‘assignment management’ tab. This can help improve student productivity, as well as remind them of the submission date of any assignments, so that they can plan accordingly. Next is to add in a ‘tests and exams reminder’ feature. This is rather straightforward, that it is to notify the users about their tests or exams time and venue. Other than that, should this project become a success, it is recommended that the implementation is expanded to all sorts of mobile platforms like the Apple’s iOS, or Microsoft’s Windows Phone OS. Additionally, a class reminder or notification is also a good addition for the application. Not to forget, the overall UI can still be improved to further enhance user ergonomics.